Program Intervensi Layanan Bimbingan Konseling melalui Kampanye Media Sosial Instagram untuk Siswa-siswi SMA X Jakarta - Kristiani, Reneta; Ardani, Aurelia; Kristofani, Amelia; Alverina, Clarissa; Fiona, Debbie; Santiara; Andrea, Zellaphro (JKI (Jurnal Konseling Indonesia), 2021)
This research discussed an intervention program for guidance counseling to reduce stigma of guidance counseling service on X School Jakarta high school students. Guidance counseling is a service provided by schools to help students grow optimally. This research aimed to see the effectiveness of social media campaigns to reduce the stigma that high school students of X School Jakarta has towards the service of guidance counseling. It also aimed to increase awareness towards the importance of mental health. This research used the approach of quantitative and qualitative analysis methods. Intervention program was a social media campaign that had been done using the feature of Instagram, such as polling and question box. The participants of this study were high school students of X School Jakarta. The result from six days of intervention showed that social media campaigns reduced the stigma towards the service of guidance counseling amongst the participants. The conclusion was that a decrease of stigma towards the guidance counseling service on high school students of X School Jakarta could be done by mental health campaigns through social media, especially Instagram.